QUALITY CONTROL OF GC PERFORMANCE FOR STEROID ANALYSIS - Suprihatin, Iryanti Eka (Jurnal Kimia (Journal of Chemistry); Vol. 5, No. 2 Juli 2011)
This paper reports the process conducted to maintain a high quality of GC responses in obtaining reliable data on steroid analyses of environmental samples. Works including setting up the Limit of Detection (LOD) and Limit of Quantitation (LOQ), maintaining linearity, controlling the reproducibility, and determining its reliability are described. It is evident that in this work the LOD of the GC is 0.0002 ng (by 1 mL injection of 0.2 mgL-1 samples) and the LOQ is 0.001 ng (by 1 mL injection of 1 mgL-1 samples), which means it is capable of detecting much lower concentrations of steroid compounds if the samples undergo 2000 times pre-concentration during preparation. Under the range investigated the GC provides reliable quantitative linear responses to all steroid compounds.
Keywords: rhizodegradation, oil waste, rate, chinetic